Effectiveness and safety of alcohol-free minoxidil in the management of treatment-naive patients with androgenetic alopecia - Patwardhan, Narendra G.; Bhide, Dhanashree; Shendkar, Sonal (International Journal of Research in Dermatology, 2024)
Background: Androgenetic alopecia (AGA) is a common dermatological condition in India, with potentially adverse psychosocial consequences. Here, we assess the effectiveness and safety of an alcohol-free, procapil-based formulation of minoxidil 5% in patients with AGA. Methods: Treatment-naïve, male patients (aged 18 to ≤45 years) with AGA were enrolled in this open-label, single-arm, non-comparative, investigator-initiated study. The change in anagen/telogen ratio (ATR), hair density, and hair shaft thickness from baseline to days 45, 90, 135 and 180, investigator and patients’ global assessment for effectiveness and tolerability, and safety were assessed. A total of 53 men were enrolled. Results: The mean (standard deviation [SD]) age of the study population was 28.3 (6.0) years. The mean (SD) ATR improvement post-treatment with minoxidil 5% was seen from day 90 (mean change: 0.4; p=0.009; 95% confidence interval [CI]: 0.1-0.7) till Day 180 (mean change: 0.4; p=0.011; 95% CI: 0.1-0.6). Improvement in hair density (p<0.01) and hair shaft thickness (p<0.01) across frontal, temporal, and occipital regions was also evident. The investigator assessment for effectiveness was ‘excellent’/’good’/’satisfactory’ for 90% of patients, which corroborated with patients’ assessment (90%) at day 180. All the investigators and patients indicated that minoxidil had ‘good’ tolerability for all patients. No adverse events were reported during the study. Conclusions: Alcohol-free minoxidil 5% was found to have a good safety profile and was efficacious in Indian male patients with AGA, with a high level of patient acceptance.